LB03.05: THE ANTI-CONTRACTILE EFFECTS OF PVAT ARE MODULATED BY AGE. THE ROLE OF NITRIC OXIDE. (June 2015) - Melrose, H.; Edwards, G.; Heagerty, A.H.; Austin, C.
Abstract : Objective: Ageing is the biggest independent risk factor for cardiovascular disease; the leading cause of death worldwide. Recent studies demonstrate that age-related endothelial dysfunction, a major risk factor for cardiovascular disease, may be due to decreased bioavailability of the endogenous vasodilator nitric oxide (NO), synthesised in the vascular endothelium by endothelial nitric oxide synthase (eNOS); which is phosphorylated and thus activated by AMP-activated protein kinase (AMPK). Vascular reactivity is further regulated via the perivascular adipose tissue (PVAT), which has a net anti-contractile effect. PVAT is known to be a source of additional NO, as well as secreting factors that augment local endothelial NO production, potentially through AMPK activation. Whilst this anti-contractile effect of PVAT is well characterised in young animals, it is unknown what effects ageing has on this relationship. Our hypothesis is that PVAT dysfunction may occur with ageing. Design and method: Small diameter mesenteric arteries were taken from male Wistar rats aged 3 months old (m.o.), 12m.o., 18m.o. and 24m.o. and contractility to U46619 (10nM-3 μM) and phenylephrine (1nM-30 μM) assessed via wire-myography in the presence and absence of PVAT and the NO-synthesis inhibitor L-NNA (50 μM). Western blotting for AMPK, p-AMPK, eNOS and p-eNOS was performed on mesenteric artery samples from rats aged 3m.o. and 24m.o. Results: Results showed that PVAT was anti-contractile in 3m.o. and 12m.o. old rats but that this effect was lost by 18m.o., remaining absent at 24m.o.. Incubation with L-NNA reversed the anti-contractile effect of PVAT at 3m.o., but not 24m.o. Expression of total AMPK was reduced in arteries from 24m.o. compared to 3m.o. whereas the ratio of p-AMPK/total AMPK remained unchanged. Expression of eNOS remained unchanged at 24m.o., whereas p-eNOS/total eNOS ratio was significantly decreased. Conclusions: The anti-contractile effect of PVAT is lost with age in rats, due at least in part to reduced NO bioavailability. This reduced bioavailability may be the result of reduced eNOS phosphorylation downstream of reduced AMPK expression.